FENOMENA 'ATH-THIBAQ' DALAM SURAT 'AL-ISRAA’': KAJIAN ILMU 'BADI’' - Ihsanudin Ihsanudin (Mahakarya: Jurnal Mahasiswa Ilmu Budaya, 2021)
The aim of this study was to describe the forms of meaning ath-thibaq or contradictions in surah al-Israa’ of the Holy Koran. The method analysis was descriptive with data collection technique by documentation. The presentation of the results of analysis is informal by describing the data in ordinary words. The urgency of this study was seeing the Holy Koran as the guidebook of all people, since it was revealed after the other holy books and the exact meaning of the Holy Koran in the context of human civilization. Thus, the Holy Koran is always explored to get its comprehensive meaning, among others by the analysis of ath-thibaq meaning. The results of this study showed 19 verses which contain ath-thibaq with 4 different forms of contradiction, i.e.: (1) contradictions of meaning in different places in verses 3 and 69; (2) contradictions of meaning in the same word in verses 8, 82, 79 , and 97; (3) contradictions of meaning in sentences, consisting of fi'il with fi'il in verse 7, isim with isim (thibaq ijab) in verses 9 and 10, 11, 15, 18 and 19, 99, 102, and 104, thibaq salab-ijab in verses 23 and 26, and thibaq ijab-salabin verse 33.